THE IMPACT OF ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE: THE CASE OF UNIVERSITY OF TECHNOLOGY AND APPLIED SCIENCES-IBRA IN OMAN - Fatma Nasser Al-Harthi; Hanin Yasser Al-Rawahi; Manar Khalfan Al-Aisari; Shamsa Said Al-Yazidi; Amal Sultan Al-Sharji (ZILLZELL MEDIA PRIMA, 2023)
Organizational culture is one of the most important factors affecting the performance of employees in various organizations. A system of values and beliefs adopted by members of the organization affects their performance either positively or negatively. This study aims to investigate the factors of organizational culture (decision-making, organizational environment & reward and recognition system) on employee job performance at UTAS- Ibra in Oman, also the study will examine the effect of the organizational culture on employee job performance at UTAS- Ibra. The method used in this study to collect data is a survey questionnaire. For the purpose of this study, 114 completed questionnaires using stratified sampling method from all academic departments and Educational Technology Center at UTAS-Ibra received and analyzed through SPSS program and smart PLS-SEM. Moreover, the study used secondary data from previous studies in different books and journals as additional sources of data. The results indicate that decision-making and the organizational environment factors of organizational culture have a positive relationship with performance. While, reward and recognition system had a negative impact on employee performance. Based on the results of the study, the study recommending that officials in UTAS-Ibra and the university should strengthen the reward and recognition system so that an integrated system is designed to make employees work in a stimulating environment for work, which results in increasing their performance.